The effect of increasing thread depth on the initial stability of dental implants : an in vitro study - Cucinelli, Chiara (2024)
Background: the long-term success of dental implants largely depends on achieving primary stability, crucial to obtain osseointegration and for immediate loading protocols. Implant thread depths seem to be one of the key factors influencing primary stability, particularly in low-density bone. Insertion torque (IT) and resonance frequency analysis (RFA) are considered the most reliable tests to assess primary stability. We evaluated how different thread depths of dental implants of the same type and brand, affect primary stability in lower bone density. We also assessed the relationship between IT and ISQ. Materials and Methods: in vitro study carried out at the University Clinic of the Universidade Católica Portuguesa of Viseu, between February 2024 and March 2024. Logistics were enabled by Megagen® Portugal, Bone Models™, SmartPeg™Osstell® and Precision Dental Medicine Platforms (CIIS-FMDUCP). 24 dental implants, divided into four groups of six implants each, with four different thread depths (Group A: 4mm, Group B: 4.5mm, Group C: 5mm, Group D: 5.5mm), were tested on three blocks of D3-type artificial bone. For each inserted implant, the IT and ISQ values were recorded. The results were statistically analyzed by calculating the mean values of IT and ISQ. The significance value was 5%. Results: from the 24 implants tested, the highest mean IT values were obtained in Group D, with an average of 54.03±8.99 N/cm2, while the lowest were in Group A with an average of 25.12±2.96 N/cm2. The mean ISQ values were consistently higher in Group D for each analyzed point (ISQ V, P, M, and D), revealing an overall mean of 70.13±1.12. Conclusions: implants with greater thread depth have been found to be more effective in achieving primary stability in lower bone density within the test conditions. Furthermore, a positive correlation has been observed between all IT and ISQ values, regardless of the thread depth.